Navigation of free-ranging automated guided vehicles by solving the hyperbolic loci of the differential times-of-flight from ultrasonic beacons - Au, Ann San (2009)
Since the late 1980s, there have been substantial interests to develop a reliable free ranging navigation system for automated guided vehicles (AGVs). The underlying motivation was to "free" the AGV from following fixed paths so that it can be truly flexible. A novel navigation system for free-ranging AGVs has been developed. It uses the differential times-of-flight from three ultrasonic transponders to determine the position of the AGV on the factory floor. The method uses the three transponders as the foci for two sets of hyperbolas. By generating the equations of these hyperbolas and solving them simultaneously, two points of intersection are obtained. Using correlation to the AGV trajectory to eliminate the redundant solution, the location of the AGV is determined. Various configurations of transponder arrangements were investigated. The first has the whole factory covered by the operation of the ultrasonic transponders, the second has the factory covered by the transponders in a checkered fashion and the third where only the nodes are covered by the transponders. It was concluded that the second layout where the transponders are arranged in a checkered fashion give the optimum use of the transponders and the transponders are more easily controlled. The Murata transducer was selected for use in the navigation system. It has an operating range of 10 metres and a beam width of 30°. The transducers are cheap and easy to operate.